A Tug of War: DNA-Sensing Antiviral Innate Immunity and Herpes Simplex Virus Type I Infection - Lin, Yingying; Zheng, Chunfu (Frontiers in Microbiology, 2019)
Cytosolic DNA sensors are the most recently described class of pattern recognition receptors (PRRs), which finally induce the transcription of type I interferons (IFN-I) and trigger the induction of a rapid and efficient innate immune response. Herpes simplex virus type I (HSV-1), a typical DNA virus, has displayed the ability to manipulate and evade host antiviral innate immune responses. Therefore, with an aim to highlight IFN-I mediated innate immune response in a battle against viral infection, here we summarize the current understanding of DNA sensing signal pathways and most recent findings on the molecular mechanisms utilized by HSV-1 to counteract antiviral immune responses. A comprehensive understanding of the interplay between HSV-1 and host early antiviral immune responses will contribute to the development of novel therapies and vaccines in the future.